PELAKSANAAN KURSUS CALON PENGANTIN (SUSCATIN) DALAM MENANGGULANGI PERCERAIAN DI KUA SINJAI UTARA KABUPATEN SINJAI - Suriyati, Suriyati; suriati, suriati; Anis, Muh.; K, Sulfikar; Riska, Riska (Jurnal Mimbar: Media Intelektual Muslim dan Bimbingan Rohani, 2024)
The aim of this research is to find out how the bride and groom course (suscatin) is implemented in dealing with divorce at KUA North Sinjai. This research is file research with a qualitative approach. The data collection method is in-depth interviews or focus groups with course participants. Data is collected and then analyzed. Based on the research results, the first thing is to increase communication with your partner, apart from communication, you can also manage conflicts that are likely to occur with your partner, there is an understanding of commitment. Couples can have a deeper understanding of the meaning of marriage and the long-term commitment needed to maintain a relationship. , then understanding roles and responsibilities. In implementing the bride and groom course, it can help couples understand their respective roles and responsibilities in marriage. Second, regarding participants' perceptions of the bride and groom course, it can vary, but overall, the course is often considered as a valuable step in preparing couples for a happy and successful married life in the future